Exploring a tristhione scorpionate ligand as a suitable chelator for the theranostic pair antimony-119 and antimony-117 - Lorraine Gaenaelle Gé; Mads Sondrup Møller; Catherine Chen; Virginia Cendán Castillo; Niels Langkjaer; Vickie McKee; Johan Hygum Dam; Christine J. McKenzie; Helge Thisgaard (SpringerOpen, 2024)
Abstract Background The highly potent Auger electron emitter antimony-119 (119Sb) and the SPECT-isotope antimony-117 (117Sb) comprise a true theranostic pair particularly suitable for cancer theranostics. Harnessing this potential requires development of a chelator that can rapidly form a stable complex with radioactive antimony ions at the low concentrations typical of radiopharmaceutical preparations. Stable Sb(III) complexes of hydrotris(methimazolyl)borate (TMe) are known, prompting our investigation of this chelator. Additionally, the production of radioantimony was optimized and the SPECT imaging properties of 117Sb was investigated, in an attempt to move towards biomedical implementation of the theranostic isotope pair of antimony. Results A method for rapid and effective labelling of TMe using 117Sb was developed, yielding high radiochemical purities of 98.5 ± 2.7% and high radionuclidic purities exceeding 99%. Radiolabelling yielded an Sb(III) complex directly from the acidic Sb(V) solution. [1XXSb]Sb-TMe in aqueous acidic solution showed high stability in the presence of cysteine, however, the stability of the radiocomplex at increased pH was significantly decreased. The production method of 117Sb was optimized, enabling a production yield of up to 19.6 MBq/µAh and the production of up to 564 MBq at end of bombardment, following irradiation of a thin 117Sn-enriched solid target. Preclinical SPECT/CT scanning of a mouse phantom containing purified 117Sb demonstrated excellent SPECT imaging properties of 117Sb with high spatial resolution comparable to that of technetium-99m. Conclusion We have explored the TMe chelator for complexation of radioantimony and devised a rapid chelation protocol suitable for the short half-life of 117Sb (T1/2 = 2.8 h). [1XXSb]Sb-TMe (1XXSb = 117Sb, 118mSb, 120mSb and 122Sb) demonstrated a high stability in presence of cysteine, although low stability was observed at pH > 4. We have achieved a production yield of 117Sb high enough for clinical applications and demonstrated the excellent SPECT-imaging properties of 117Sb. The results contribute valuable information for the development of suitable chelators for radioantimony and is a step further towards implementation of the antimony theranostic pair in biomedical applications.